Trend on dental caries status and its risk indicators in children aged 12 years in China: a multilevel analysis based on the repeated national cross-sectional surveys in 2005 and 2015 - Fei Li; Si-Cheng Wu; Zhi-Yuan Zhang; Edward Chin Man Lo; Wen-Jia Gu; Dan-Ying Tao; Xing Wang; Bao-Jun Tai; De-Yu Hu; Huan-Cai Lin; Bo Wang; Yan Si; et al. (BMC, 2021)
Abstract Background This study aimed to explore the trend and risk indicators for dental caries of children aged 12 years in China based on national oral health survey data in 2005 and 2015. Methods Research data were from the two latest national oral health surveys conducted in mainland China, including 30 and 31 provinces, autonomous regions, and municipalities in 2005 and 2015, respectively. Children aged 12 years were clinically examined for dental caries and dental fluorosis according to the World Health Organization criteria. Sociodemographic characteristics and oral health-related behaviours were collected using questionnaires. Multilevel zero-inflated negative binomial regression model was used to investigate the association between dental caries severity and dental fluorosis, sociodemographic characteristics, and oral health-related behaviours. Results The final analyses included 12,350 and 27,818 children surveyed in 2005 and 2015, respectively. The standardized prevalence of dental caries increased from 27.05% (95% confidence interval [CI], 24.25-28.85) in 2005 to 37.92% (95% CI, 34.94-40.90) in 2015, and the respective standardized mean decayed, missing, filled teeth (DMFT) index scores increased from 0.50 (standard deviation [SD], 1.04) to 0.83 (SD, 1.45) (P < 0.001). Fujian province had the highest increase in dental caries, followed by Liaoning, Heilongjiang, Hainan, and Yunnan. Results revealed that children who were girls, more frequently experienced dental pain, and had more recent dental visits, had significantly higher DMFT scores after adjusting for the survey year and other variables (all P < 0.05). Conclusions Dental caries of 12-year-old children in China deteriorated from 2005 to 2015, particularly in the northeast and southwest regions. Dental caries was associated with sex, dental pain, and dental service utilization.